Valorization of bio-calcium carbonate based Chamelea gallina shell waste fillers in shape memory polymer composites - Pekdemir, Sibel Selcuk; Onay, Hatice; Oner, Ecem Ozen; Pekdemir, Mustafa Ersin; Kok, Mediha; Ates, Burhan; Dalgic, Goktug (Wiley, 2024)
In recent years, the focus has been on the use of calcium carbonate-based seashell wastes in the production of new thermoplastic and thermoset polymer materials, paving the way for their use as biofillers in polymeric composites. In this study, it is aimed to obtain a new polymeric composite material by doping Chamelea gallina shells, on polylactic acid (PLA)/polyethylene glycol (PEG) blend. Structural characterization of the obtained PLA/PEG blend/C. gallina composite films was performed with attenuated total reflection infrared spectroscopy (ATR-IR). When the thermal properties of composite materials were examined by thermogravimetric analysis (TGA), it was determined that the thermal stability of polymeric composites increased with the addition of C. gallina. SEM images showed that the polymer blend films, which appeared to have a porous structure, filled the pores with increasing C. gallina ratio. It was observed that the biodegradability of PLA/PEG blend composite films decreased with increasing C. gallina shells addition. However, C. gallina had a positive effect on the swelling and water absorption capacities of polymeric composites. The increase in tensile strength and elongation at break values of PLA/PEG blend/C. gallina composite films with increasing C. gallina means that the mechanical properties of the polymer are improved.
Keywords: biodegradable; Chamelea gallina; PLA/PEG blend; polymer filler; shape memory